Seeing is Believing: How the Layering of Race is Obscured by "White Epistemologies" in the Criminal Justice Field. Issue 2 (18th July 2022) - Parmar, Alpa; Earle, Rod; Phillips, Coretta
Abstract: Criminology has been slow in recognizing the central organizing logic of race in (post)colonial societies. It is therefore unsurprising that research practice falls behind that proffered through other disciplinary epistemological critiques. In this paper, we interrogate the tools of whiteness that are obscured in the widely used research method of in-depth interviews. We scrutinize what is not "seen" but which can be made evident in research interactions, using three interview case studies conducted in England. Warren, a white man interviewed by a white man (Earle), exposes the occlusions and upholding of race and racism in prison settings. Rafan, a British Bangladeshi man interviewed by a British Indian woman (Parmar) reveals a socio-cultural backstory in which coloniality is deeply implicated but seems just beyond view, within and outwith the criminal justice system. Finally, the interview of Cairo, a black (British) Jamaican man by a mixed-race black British woman (Phillips), articulates a poignant yet defiant response to structural and cultural racism, which begins long before interaction with the criminal justice system. Laid bare are the limitations of existing research where over-represented white researchers typically conduct research involving under-represented minorities who are vulnerable to exclusion, criminalization, and state violence. Our three case study interviews offer a step beyond traditional qualitative research instruction for students and apprentice researchers. It aims to impart a reflexive pedagogy which intertwines biography with politics in training the next generation of criminal justice researchers.